Advances in management accounting - Akroyd, Chris (Associate professor of accounting) (Advances in management accounting ;, 2023)
Volume 35 of Advances in Management Accounting uses a variety of methods, from experiments and case studies to surveys, to build upon existing knowledge within the management accounting discipline. Containing a diverse range of authors from Australia, Canada, New Zealand and the United States of America, this publication focuses on theoretically sound and practical research which has a cutting-edge and wide-reaching appeal to academics and practitioners. Showcasing chapters on planning and budgeting processes, costing systems, strategic management accounting practices and performance management, this edited collection will appeal to both management accounting academics and professionals. Topics analyzed include the new management accounting ecosystem, strategic planning and budgeting, complex cost accounting systems, non-monetary preferences and cost reporting, strategic management accounting practices, customer centered strategy and relative performance information in remote work arrangements. Advances in Management Accounting (AIMA) publishes thought-provoking volumes that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. The series seeks thoughtful, well-developed articles on a variety of current topics in management accounting, broadly defined. AIMA seeks to publish commentaries on research methodology and new management accounting areas of interest as well as papers using research methods including survey research, field tests, case studies, experiments, meta-analyses, and modeling.